Sosialisasi Sertifikasi Halal Dan Jaminan Halal Pada Umkm Makanan Dan Minuman Di Kabupaten Gresik - Asyik, Nur Fadjrih; Patuh, Maswar; Triyonowati; Yahya; Respatia, Wimba (Fakultas Ekonomi Universitas Islam Majapahit, 2023)
A halal certificate on a product is now a must. Consumers will be more selective in choosing products that have halal certification for consumption. The socialization and assistance activities for Halal Certification and Halal Assurance were carried out for Food and Beverage MSME partners assisted by DMI, Gresik Regency. The purpose of this community service activity is to provide an understanding of the urgency of halal, halal ingredients, halal potential, and halal certification so that it can be used as a medium for developing businesses and increasing sales turnover. The ABDIMAS implementation method includes three stages: The planning stage involves mapping the problem, solving problems, and coordinating with MSME partners and DMI Gresik Regency. The stage of implementing the socialization of halal certification using the lecture and question-and-answer method. The monitoring and evaluation phase of a series of socialization and mentoring activities carried out. The results of ABDIMAS activities show that MSME partners participating in the socialization are quite enthusiastic about asking questions related to halal products, the benefits of halal labeled products, halal certification procedures, and halal product guarantees. It is hoped that the food and beverage MSMEs assisted by DMI Gresik Regency can arrange halal certification both through the regular and self-declare routes so as to increase sales turnover.